1989
DOI: 10.1111/j.1600-9657.1989.tb00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory resorption: untreated, arrested, prevented

Abstract: Three human replantation cases are presented wherein the results are in accord with the literature concerning inflammatory resorption and calcium hydroxide therapy. The cases unintentionally simulate a designed experiment wherein the control case received no treatment and the other 2 were subjected to independent variables such as obturation in the hand and the timing of the calcium hydroxide therapy. The untreated case resulted in loss of the tooth, while manipulation of variables in the other two resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Gutta-percha is the most frequently used root canal filling material (9,28,36,(39)(40)(41)(42)(43) in combination with zinc oxide and eugenol-based sealers (21,22,34,44,45) and CH-based sealers, such as Sealapex (37,38,46). The use of mineral trioxide aggregate (MTA) has also been investigated in immediate tooth replantation (47).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gutta-percha is the most frequently used root canal filling material (9,28,36,(39)(40)(41)(42)(43) in combination with zinc oxide and eugenol-based sealers (21,22,34,44,45) and CH-based sealers, such as Sealapex (37,38,46). The use of mineral trioxide aggregate (MTA) has also been investigated in immediate tooth replantation (47).…”
Section: Literature Reviewmentioning
confidence: 99%
“…tory root resorption. Several studies (10,(12)(13)(14)(15)(16)(17)(18)(19) have demonstrated that root resorption secondary to replantation may be prevented or controlled with endodontic therapy, and several substances have been used for such purpose (9,12,14,15,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). This article presents a literature review on intracanal dressings and root canal filling materials used in cases of tooth replantation.…”
mentioning
confidence: 99%